1990
DOI: 10.1172/jci114469
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics of the variable regions of immunoglobulin genes encoding a pathogenic autoantibody in murine lupus.

Abstract: We have studied several monoclonal anti-double-stranded (ds) DNA antibodies for their ability to accelerate lupus nephritis in young NZB X NZW Fl female mice and to induce it in BALB/c mice. Two identified as pathogens in both strains have characteristics previously associated with nephritogenicity: expression of IgG2a isotype and IdGN2 idiotype. Both pathogenic antibodies used the combination of genes from the VHJ558 and VK9 subfamilies. Two weak pathogens failed to accelerate nephritis in young BW mice, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 70 publications
0
86
0
Order By: Relevance
“…Hahn and coworkers (19)(20)(21) found that a peptide of an anti-DNA mAb A6.1 isolated from NZB͞W mice was involved in pathogenic and autoimmune processes in the mice. Thus, immunization of NZB͞W mice with the latter CDR2 peptide, as well as with a cryptic peptide of the same antibody, increased plasma levels of anti-DNA IgG antibodies, accelerating immune complex deposition in the kidneys and nephritis (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Hahn and coworkers (19)(20)(21) found that a peptide of an anti-DNA mAb A6.1 isolated from NZB͞W mice was involved in pathogenic and autoimmune processes in the mice. Thus, immunization of NZB͞W mice with the latter CDR2 peptide, as well as with a cryptic peptide of the same antibody, increased plasma levels of anti-DNA IgG antibodies, accelerating immune complex deposition in the kidneys and nephritis (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…2). Further, mouse 21 had a clonally related family (19/120), with the conserved CDR3 motif YYGSS associated with anti-DNA/nucleosome binding (40). This family expressed YYYGSSR (Fig.…”
Section: Anti-dsdna B Cells Are Markedly Expanded In Mice Undergoing mentioning
confidence: 98%
“…7 pCons (FIEWNKLRFRQGLEW), the artificial tolerizing peptide, contains T-cell determinants based on the J558 V H regions of several murine mAb anti-dsDNA from BWF1 mice. 27,69,70 Peptides were synthesized at Chiron Biochemicals (San Diego, CA, USA), purified to a single peak on high-performance liquid chromatography, and analyzed by mass spectroscopy for expected amino acid content.…”
Section: Peptidesmentioning
confidence: 99%